Therapeutic Effect of Schistosoma japonicum Cystatin on Atherosclerotic Renal Damage - Yang, Huijuan; Li, Hongqi; Chen, Weidong; Mei, Zhijie; Yuan, Yuan; Wang, Xiaoli; Chu, Liang; Xu, Yu; Sun, Yan; Li, Dingru; Gao, Hongyu; Zhan, Bin; et al. (Frontiers in Cell and Developmental Biology, 2021)
Atherosclerosis is a chronic inflammation of the arterial vessel wall driven by lipid metabolism disorders. Although helminth infection and their derivatives have been identified to attenuate the chronic inflammatory diseases, the immunomodulatory effect of recombinant Schistosoma japonicum cystatin (rSj-Cys) on metabolic diseases and atherosclerosis has not been reported. In this study, we investigated the therapeutic efficacy of rSj-Cys on atherosclerotic renal damage and explored the related immunological mechanism. The results demonstrated that treatment with rSj-Cys significantly reduced body weight gain, hyperlipidemia and atherosclerosis induced by the high-fat diet in apoE−/− mice. The treatment of rSj-Cys also significantly improved kidney functions through promoting macrophage polarization from M1 to M2, therefore inhibiting M1 macrophage-induced inflammation. The possible mechanism underlying the regulatory effect of rSj-Cys on reducing atherosclerosis and atherosclerotic renal damage is that rSj-Cys stimulates Treg and M2 macrophage polarization that produce regulatory cytokines, such as IL-10 and TGF-β. The therapeutic effect of rSj-Cys on atherosclerotic renal damage possibly through inhibiting the activation of TLR2/Myd88 signaling pathway. The results in this study provide evidences for the first time that Schistosoma-derived cystatin could be developed as a therapeutic agent to treat lipid metabolism disorder and atherosclerosis that threats million’s lives around the world.